Pemberian Pupuk Kandang Ayam dan ZPT Jimmy Hantu Terhadap Pertumbuhan dan Produksi Jagung Manis (Zea mays saccharata L Sturt.) - Muhammad Hafizd; Nurma ani; Dermawan Hutagaol (Jurnal Agrofolium, 2026)
Corn has the potential to perform various functions, such as producing food, animal feed, and raw materials for various industries, making it a leading agribusiness commodity. In an effort to improve farmers' income and welfare through the application of technology, production, and post-harvest management, it is crucial to understand and understand the prospects for commercial-scale corn cultivation. The purpose of this study is to determine the effect of the application of Chicken Manure and ZPT Jimmy Hantu on the growth and production of sweet corn plants (Zea mays saccharata L Sturt.). This study employed a Randomized Block Design (RBD). The analytical method used to draw conclusions was derived from data analysis conducted using a mathematical linear model. The results of the study show that 1). Chicken manure had a significant impact on plant height, leaf area, cob length with husk, and cob diameter; however, it had no significant impact on cob weight with husk per sample and plot. 2). The administration of ZPT jimmy hantu has an unreal effect on all observed parameters. 3). The interaction between chicken manure and plant fertilizer significantly affected plant height, leaf area, cob length, and cob diameter. However, this effect was not significant for cob weight per sample and plot, or the Jimmy Hantu plant growth regulator (PGR).